Investigating, identifying and evaluating organizational and infrastructural strategic factors affecting organizational management processes from the perspective of productivity management - Ali Mosayeb moradi; Neda Ahmad Khan Beigi (goodwood publishing)
Purpose: The purpose of this present study is to investigate the impact of institutional and infrastructural factors on knowledge management processes from the perspective of Nonaka and Takeuchi with a case study of design offices of a product organization. Research methodology: The research is applied and is a descriptive survey in terms of data collection. The statistical population of the design offices of a product organization consisted of 75 people and the statistical sample was estimated 63 people. The research tool was a researcher-made questionnaire with a reliability of 77%. Results: The findings show that seven institutional and infrastructure factors affecting knowledge management processes were identified. Also prioritization by TOPSIS showed that organizational structure, culture and values, above average, can be deployed in the design office, and knowledge management policies and guidance are average, but information technology is below average. Limitation: The results extend the understanding of the role of quality of work-life in organizational effectiveness. The research findings have implications for human resource managers. Contribution: The results of the study help the human resource managers of organizations to identify the elements that affect the quality of work-life and help them in planning to increase organizational effectiveness by increasing employee satisfaction and motivation. Keywords: Knowledge management, Institution, Infrastructure, Nonaka and Takeuchi